Pengaruh Media Pohon Huruf Bersries Terhadap Kemampuan Membaca Permulaan Anak Usia Dini Membaca Permulaan Anak Usia Dini 5-6 Tahun Di TKQ Baitul Amal Karawang - Wahyuni, Nuri; Darmiyanti, Astuti; Riana, Nancy (Peneliti.net, 2025)
This study discusses the impact of Media Tree Letter series on Early reading skills of Early childhood 5-6 Years old at TKQ Baitul Amal Karawang. Media Tree Letter series is an educational media, particularly visual media made of a board that has a painted tree shape and is implemented with green flannel material the use of used bottle caps, there are letter carvings on the tree, prepared with coloured letter shapes, picture cards and dimension cards with real doll shapes. This media tree letter series has numerous series, the media designed objectives to increase early reading talents which includes recognizing letter symbols, recognizing prefixes, distinguishing the relationship between sounds and letters, composing syllables, being able to make simple writing, composing words into sentences and media tree letter series can also compose letter puzzles. The research method used is a quantitative method with a pre-experimental one group pretest posttest layout studies type. The populace in this study became group B at TKQ Baitul Amal Karawang. The sample in this look at was 16 children. data series performed in this study was first with an preliminary test (pretest), then treatment was done which in this study was achieved 8 times treatment, and a very last test (posttest). The statistics analysis method used become descriptive statistical analysis, Shapirio Wilk normality test, homogeneity test and hypothesis check the use of paired same sample t test. based on the results of this study, it can be concluded that the early studying ability of early childhood aged five-6 years. that is evidenced by the results of the paired sample t test, namely the t count value of 28,920 and t desk 1,753 this means that that the t count price ≥ t desk. the rule that was decided was Ha accepted and H0 rejected. And sig. (2-tailed) 0.001 <0.05, then the guideline that was decided was then H0 rejected and Ha normal which means that the use of the berseries letter tree media has a significant influence at the early reading ability of early childhood aged five-6 years at TKQ Baitul Amal Karawang. in this way, the use of this media can help children develop their initial reading skills. Early Childhood, beginning Reading , Letter Tree Series.